Impact of microsatellite based selection on grower and layer economic traits in Rhode Island Red chicken - DEBNATH, JOWEL; KUMAR, SANJEEV; DAS, ANANTA KUMAR; RAHIM, ABDUL (The Indian Journal of Animal Sciences, 2021)
The present study aimed to assess impact of selection based on microsatellite-genotypes at ADL0176 and the association of microsatellite-genotypes at ADL0176 and MCW0044 located on chromosome number-2 with growth and layer economic traits in RIR chicken could reveal impact when the sire component influenced the growth and layer economic traits of the progeny-birds with different genotypes at ADL0176 and MCW0044 microsatellites. DD, EE and CC/AD-genotypes at ADL0176 microsatellite had corresponding higher BW28, BW40 and EW40 of the progeny than other genotypes, while BB-genotype at MCW0044 had higher BW40. Present findings could suggest the use of microsatellite-marker based selection for faster genetic improvement of economic traits in RIR chicken, provided its validation by taking larger sample sizes.